Investigação de polimorfismos nos genes abcc1, abcc2 e abcc3 em pacientes com leucemia mieloide crônica utilizando inibidores de tirosina quinase no Amapá - ESPINDOLA, Gabriel de Oliveira (UNIFAP - Universidade Federal do Amapá, 2022)
Chronic Myeloid Leukemia is a myeloproliferative abnormality that affects blood cells. Found in over 95% of Chronic Myeloid Leukemiacases, the Philadelphia Chromosome is the result of reciprocal translocation between chromosomes 9 and 22 (t9,22), being the first neoplasm whose development was related to Philadelphia Chromosome. Tyrosine kinase are the first lines of treatment for chronic Myeloid Leukemia, but failures in therapeutic responses are associated with the presence of genetic variability in metabolic pathways. DNA polymorphisms observed in transporter genes are investigated as influencing factors for the variability of responses to Tyrosine kinase Inibidors and can be considered molecular markers of pharmacogenetic relevance. The aim of this study was to conduct an epidemiological survey and to investigate the allelic distribution of polymorphisms in the multidrug resistance genes: ABCC1, ABCC2 and ABCC3, in biological samples collected from Chronic Myeloid Leukemia patients undergoing Tyrosine kinase Inibidors in the city of Macapá / AP The epidemiological survey was performed through medical records research and the application of questionnaires to patients. Molecular investigation was performed by collecting peripheral blood and oral scraping in patients from the Dr. Alberto Lima Clinical Hospital. The sample DNA was extracted by the Mebep Bioscience Blood Kit / Tissue DNA Mini Kit (Ludwing Biotec). Genotyping was performed by the Life Technologies (California, USA) QuantStudio 12K flex system on 20 biological samples. The observed epidemiological data indicated a higher incidence of cases in the city of Macapá, in male groups, in addition to patients under the age of 45 (median of 38.5 years) and with a median age of diagnosis of 3.5 years. Responses to treatment indicated that 65% of patients achieved good response to Imatinib therapies, achieving a median treatment time of 3.5 years. SNP genotyping did not indicate significant statistical associations for the clinical outcomes raised by the study with the investigated genotypes. Despite obtaining unprecedented epidemiological information, more molecular studies are needed in mixed populations such as this study, helping to expand knowledge about the pharmacogenetic data of the Brazilian population.